Pengaruh Jenis Pemlastis dan Konsentrasi Penguat Polivinil Alkohol terhadap Karakteristik Komposit Bioplastik Pati Talas (Colocasia esculenta L) dan Karagenan - Risky Simarmata; Amna Hartiati; Nyoman Semadi Antara (Fakultas Teknologi Pertanian, Universitas Udayana Gedung GA, Fakultas Teknologi Pertanian, Universitas Udayana Jl. Raya Bukit Jimbaran, Jimbaran, Kuta Selatan, Bali Telp/Fax: (0361) 701801, 2023)
This study aims to determine the effect of plasticizer type concentration and reinforcement material concentration on the characteristics of bioplastic composites, to determine the treatment of plasticizer type concentrations consisting of two types, namely castor oil and stearic acid plasticizers, as well as the concentration of polyvinyl alcohol reinforcement which produces the best treated bioplastic composites and to identify best treatment bioplastic composite functional groups. This study used a factorial randomized block design with two factors, namely the type of plasticizer and its concentration which consisted of 3 levels (8.33; 16.67; 25%) and the concentration of polyvinyl alcohol reinforcement (5; 10: 15%). 18 treatment combinations were obtained which were grouped into 2 base on the time of making bioplastics, resulting in a total of 36 treatment units. The variables observed were tensile strength, elongation at break, elasticity, thickness expansion, biodegradation, and identification of functional groups. The data obtained were analyzed for diversity and continued with the Honest Significant Difference test. The results showed that the type of plasticizer and concentration of reinforcement had a very significant effect on the tensile strength, elongation at break, elasticity, and thickness expansion, but had no significant effect on the biodegradation time. The best bioplastic composite characteristics were the result of treatment with a concentration of 1 g castor oil plasticizer and 15 g PVA concentration with a tensile strength value of 15.76 MPa, elongation at break of 8.51%, elasticity of 185.17 MPa, thickness expansion of 50.35 %, biodegradation time is 5 days and contains (C – H) alkene groups, (C – O) alcohol groups, (C = C) alkene groups, (C – H) alkene groups and (O – H) hydroxyl groups.